E. coli and S. aureus resist silver nanoparticles via an identical mechanism, but through different pathways - Hochvaldová, Lucie; Panáček, David; Válková, Lucie; Večeřová, Renata; Kolář, Milan; Prucek, Robert; Kvítek, Libor; Panáček, Aleš (Communications biology, 2024)
Nanostructured materials with antibacterial activity face the same threat as conventional antibiotics - bacterial resistance, which reduces their effectiveness. However, unlike antibiotics, research into the emergence and mechanisms of bacterial resistance to antibacterial nanomaterials is still in its early stages. Here we show how Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli bacteria develop resistance to silver nanoparticles, resulting in an increase in the minimum inhibitory concentration from 1.69 mg/L for S. aureus and 3.38 mg/L for E. coli to 54 mg/L with repeated exposure over 12 and 6 cultivation steps, respectively. The mechanism of resistance is the same for both types of bacteria and involves the aggregation of silver nanoparticles leading to the formation of black precipitates. However, the way in which Gram-positive and Gram-negative bacteria induce aggregation of silver nanoparticles is completely different. Chemical analysis of the surface of the silver precipitates shows that aggregation is triggered by flagellin production in E. coli and by bacterial biofilm formation in S. aureus. However, resistance in both types of bacteria can be overcome by using pomegranate rind extract, which inhibits both flagellin and biofilm production, or by stabilizing the silver nanoparticles by covalently binding them to a composite material containing graphene sheets, which protects the silver nanoparticles from aggregation induced by the bacterial biofilm produced by S. aureus. This research improves the understanding of bacterial resistance mechanisms to nanostructured materials, which differ from resistance mechanisms to conventional antibiotics, and provides potential strategies to combat bacterial resistance and develop more effective antimicrobial treatments.
Keywords: Staphylococcus aureus; Silver; Drug Resistance, Bacterial; bakteriální léková rezistence; mikrobiální testy citlivosti; biofilmy; Microbial Sensitivity Tests; antibakteriální látky; Anti-Bacterial Agents; Biofilms; stříbro; Escherichia coli; kovové nanočástice; Metal Nanoparticles